2004
DOI: 10.1111/j.0031-9317.2004.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of 5‐aminolevulinic acid on photosynthesis of melon (Cucumis melo) seedlings under low light and chilling stress conditions

Abstract: When melon seedlings (Cucumis melo L. Ximiya No. 1) were cultured in a growth chamber with about 150 micro mol m(-2) s(-1) photon flux density, the leaf photosynthetic ability reduced dramatically as leaf position decreased from the top. The application of 5-aminolevulinic acid (ALA) solutions significantly increased the net photosynthetic rate (P(n)) as well as apparent quantum yield (AQY), carboxylation efficiency (CE) and stomata conductance (G(s)). After irrigation with 10 ml of ALA solution (10 mg l(-1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 19 publications
6
79
0
Order By: Relevance
“…Biomass of photosynthetic bacteria has been used as a source of protein with high amounts of essential amino acids e.g., methionine and lysine, 5,6) and also as a feed supplement for producing low-cholesterol chicken eggs. 7) ALA can be applied as a plant growth-regulator and as a weed growth inhibitor, 1) in which a concentration range of 0.06-0.6 mM demonstrated plant regulating activities 8) whereas 4 mM ALA could be used to control weed (Trifolium repens) growth. 9) Application of ALA to date palm revealed that the fruit chlorophyll content at the Khalal stage was significantly increased.…”
Section: Influence Of Precursors and Inhibitor On The Production Of Ementioning
confidence: 99%
See 1 more Smart Citation
“…Biomass of photosynthetic bacteria has been used as a source of protein with high amounts of essential amino acids e.g., methionine and lysine, 5,6) and also as a feed supplement for producing low-cholesterol chicken eggs. 7) ALA can be applied as a plant growth-regulator and as a weed growth inhibitor, 1) in which a concentration range of 0.06-0.6 mM demonstrated plant regulating activities 8) whereas 4 mM ALA could be used to control weed (Trifolium repens) growth. 9) Application of ALA to date palm revealed that the fruit chlorophyll content at the Khalal stage was significantly increased.…”
Section: Influence Of Precursors and Inhibitor On The Production Of Ementioning
confidence: 99%
“…It should be emphasized that the ALA content obtained in this study was enough to be used to promote plant growth. 8) The growth of the bacterium under the optimal conditions is shown in Fig. 2b.…”
Section: )mentioning
confidence: 99%
“…This means that ALA treatment did not only promote stomatal opening, but also affect the non-stomatal factors related with photosynthesis (Farquhar and Sharkey, 1982). In other studies, exogenous ALA promotion on stomatal opening has been reported in melon (Wang et al, 2004a) or watermelon . A transgenic tobacco, which could over-produce endogenous ALA, also possessed higher stomatal conductivity (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 73%
“…Xu et al (2010) suggested that ALA at low concentrations could increase the growth of kudzu Pueraria phaseoloides) by increasing photosynthetic rate. Previous studies have shown that low concentrations of exogenous ALA promote plant growth, development, and responses to environmental stresses (Bindu and Vivekanandan, 1998), such as crop productivity (Hotta et al, 1997a) and stress tolerance (Hotta et al, 1998;Watanabe et al, 2000;Wang et al, 2004;Sun et al, 2009;Liu et al, 2011;Naeem et al, 2011). These previous studies suggest that the effect of ALA on plants depends on the concentration of ALA. ALA at low concentrations is known to promote growth and development of some plants, animals, algae and photosynthetic bacteria (Chakraborty and Tripathy, 1990;Balestrasse et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…Exogenous ALA can enhance the quality of some medicinal plants (Xu et al, 2010;Xu and Cheng, 2011) and enhance the photosynthetic rate, chlorophyll content, and yield of lettuce (Xu et al, 2012). ALA has been proposed as a novel natural and environmentally friendly regulator that is widely used in agriculture (Wang et al, 2004). This compound appears to act as a hormonelike plant growth regulator and is effective at relatively low concentrations (Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%